Mediation of processes of systems codesign and the empowerment of lesbian, gay, bisexual, and transgender (LGBT) people : Mediação de processos de codesign de sistemas e o empoderamento de pessoas lésbicas, gays, bissexuais e transgêneras (LGBT) - Pereira, Guilherme Colucci, 1992- (2018)
Orientador: Maria Cecilia Calani Baranauskas